2020
DOI: 10.3390/toxins12090608
|View full text |Cite
|
Sign up to set email alerts
|

The Parotoid Gland Secretion from Peruvian Toad Rhinella horribilis (Wiegmann, 1833): Chemical Composition and Effect on the Proliferation and Migration of Lung Cancer Cells

Abstract: Since Rhinella sp. toads produce bioactive substances, some species have been used in traditional medicine and magical practices by ancient cultures in Peru. During several decades, the Rhinella horribilis toad was confused with the invasive toad Rhinella marina, a species documented with extensive toxinological studies. In contrast, the chemical composition and biological effects of the parotoid gland secretions (PGS) remain still unknown for R. horribilis. In this work, we determine for the first time 55 com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…These compounds inhibited the growth of the Batrachochytrium dendrobatidis strain, and their MIC were 12.9, 50.0, and 14.3 μM, respectively [ 7 ]. These bufadienolides were also identified in Rhinella horribilis [ 52 ]. The discovery of these compounds, effective against these fungal strains, will allow the development of therapeutic agents that treat infections caused in humans and other animals [ 53 ].…”
Section: Antimicrobial Activities Of Compounds From Toads’ Cutaneous ...mentioning
confidence: 99%
“…These compounds inhibited the growth of the Batrachochytrium dendrobatidis strain, and their MIC were 12.9, 50.0, and 14.3 μM, respectively [ 7 ]. These bufadienolides were also identified in Rhinella horribilis [ 52 ]. The discovery of these compounds, effective against these fungal strains, will allow the development of therapeutic agents that treat infections caused in humans and other animals [ 53 ].…”
Section: Antimicrobial Activities Of Compounds From Toads’ Cutaneous ...mentioning
confidence: 99%
“…They were found in the parotoid gland secretion (PGS) of Rhinella horribilis together with alkaloids and argininyl diacids (Schmeda‐Hirschmann et al, 2020). Marinobufagin was identified as the main bufadienolide in R. marina the Peruvian Amazon toad.…”
Section: Introductionsmentioning
confidence: 99%
“…The argininyl diacid derivatives of telocinobufagin, hellebrigenin, bufotalinin, and resibufogenin were also present in this Amazonian toad. Studying their anticancer effects revealed that changes in the production of reactive oxygen species (ROS) and cell cycle arrest mediate the proliferation of MCF7 and MDA‐MB‐231 breast cancer cells (Schmeda‐Hirschmann et al, 2020). Bufalin, telocinobufagin, cinobufagin, and marinobufagin were reported to be the most common bufadienolides in the venom of toads.…”
Section: Introductionsmentioning
confidence: 99%
“…Thus, three papers describe the effects of toad poisons. For example, in the parotoid gland secretion of the toad Rhinella horribilis, more than 50 compounds (including alkaloids, bufadienolides, and argininyl diacids derivatives) are identified using HPLC-MS/MS [1]. The secretion and one of its fractions manifest antiproliferative activity against A549 cancer cells.…”
mentioning
confidence: 99%